Effects of mode of reproduction on genetic polymorphism and divergence in wild yams (Dioscoreaceae: Dioscorea) - Xin Wang; Qing-Hong Feng; Zhi-Hua Zeng; Zhi-Qiang Zhang; Jie Cai; Gao Chen; De-Zhu Li; Hong Wang; Wei Zhou (Plant Diversity)
Evolutionary transitions from sexual to asexual reproduction should have significant influences on genetic divergence and polymorphism at the genome level. Plant lineages with diverse reproductive systems provide opportunities to investigate this question using comparative approaches and studies of molecular evolution. We investigated evidence for differences among the transcriptomes of 19 Dioscorea species (wild yams) with diverse reproductive systems. These included sexual species, those that propagate primarily by bulbils, and those with mixed sexual and asexual reproductive modes. We examined how transitions between these reproductive systems affected between-species divergence and within-species polymorphism. Primarily asexual species exhibited a reduced efficacy of natural selection and accumulation of deleterious mutations for both divergence and polymorphism. In contrast, species with mixed reproductive strategies involving both seed and clonal reproduction showed no evidence of an increased fixation of harmful mutations at the divergence level, while an accumulation of genetic load present in polymorphism was evident. Our study indicates that the genetic consequences of evolutionary transitions from sexual to predominantly clonal reproduction is likely to depend on both the duration and extent of asexuality occurring in populations.